The Effect of Customer Behavior and Social Presence in TikTok Live Shopping on Purchase Intention, With Customer Trust A Mediator - Desi Kumala Sari Desi; Ratih Amelia; Nur Pratiwi (Journal of Digital Business and Innovation Management, 2026)
The research aims to analyze the influence of Customer Behavior and Social Presence on Purchase Intention in TikTok Live Shopping, with Customer Trust as the mediating variable. This research was motivated by the phenomenon of the gap between high user engagement and low purchase conversion in live commerce, given Indonesia’s position as the biggest TikTok user country in the world. Using a quantitative approach grounded in the Stimulus-Organism-Response (S-O-R) theory, data were collected from 336 undergraduate students at the Faculty of Economics and Business, UNESA, through cluster sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that Customer Behavior and Social Presence have a positive and significant influence on Purchase Intention, directly and through the mediation of Customer Trust. These findings indicate that Customer Trust acts as a significant mediating mechanism linking consumer behavior and social presence to purchase intention in the social commerce ecosystem.